Perancangan Furniture Fungsional Home Office Untuk Desainer Interior - Christianto Ciabrata Alfons (Intra, 2017)
As time passes, it brings us into the modern era that becomes instant and also affects everything that has been done from different perspectives. This will be very helpful especially in the field of home office. With a positive impact that can be applied in the home office area with multifunctional furniture that can accommodate user activity. This multifunctional furniture design also takes into account several things such as ergonomics and sustainability that can be perceived by users who are safe and comfortable. Then this can make timely efficiency to make operations more productive. Therefore, the office no longer requires a large room, enough with a mini space that can create a more functional home office area without wasting space.